2020
DOI: 10.1021/acsanm.0c00872
|View full text |Cite
|
Sign up to set email alerts
|

Octupolar Plasmonic Nanosensor Based on Ordered Arrays of Triangular Au Nanopillars for Selective Rotavirus Detection

Abstract: Technologies based on plasmonic nanostructures are a rapidly growing field that aims to be a valid alternative to conventional diagnostic tools. One of the main goals in their technological development consists of the design of systems for sensitive and specific detection of pathogens in water. Among these, rotaviruses represent the main cause of childhood viral gastroenteritis in humans. In this work, we design functionalized plasmonic label-free nanosensors based on localized surface plasmon resonance (LSPR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Nanostructured Au substrates were fabricated by following a procedure identical to the one already described. 19 Briefly, 300 μm × 300 μm Au nanostructures were fabricated by a high-resolution electron beam lithography (EBL) system (Raith 150 EBL system), using a 78 nm layer of styrene methyl acrylate (ZEP 520A) as positive resist. The resist was spin-coated on 2 × 2 cm glass slides covered with a 15 nm indium tin oxide (ITO) conductive layer and baked at 170 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Nanostructured Au substrates were fabricated by following a procedure identical to the one already described. 19 Briefly, 300 μm × 300 μm Au nanostructures were fabricated by a high-resolution electron beam lithography (EBL) system (Raith 150 EBL system), using a 78 nm layer of styrene methyl acrylate (ZEP 520A) as positive resist. The resist was spin-coated on 2 × 2 cm glass slides covered with a 15 nm indium tin oxide (ITO) conductive layer and baked at 170 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, different kinds of optical biosensors such as surface plasmon resonance (SPR), optical fibers, adsorption, fluorescent, and luminescence are currently available in the literature and on the market [ 98 ]. Nevertheless, the SPR strategy is the most known and used version of optical biosensors for the diagnosis of gastroenteritis viruses in publications [ 99 , 100 , 101 ].…”
Section: Investigation Of Various Biosensing Platforms For Detection ...mentioning
confidence: 99%
“…SERS can be employed for direct spectroscopic characterisation, using non-functionalised nanostructured substrates. In 2001, Bao et al conducted a SERS study of insect nuclear polyhedrosis viruses in silver hydrogels [92] , while numerous other studies have used nanostructured metal substrates to study molecular signatures of, for example, respiratory viruses [93] , [94] , rotavirus [95] , [96] and poxviridae virions [97] . Fan et al demonstrated the use of SERS to detect and discriminate seven food and waterborne viruses in aqueous solution, including noro virus, adeno virus, parvo virus, rota virus, corona virus, paramyxo virus, and herpes virus [98] .…”
Section: Vibrational Spectroscopic Analysis Of Viruses and Viral Infe...mentioning
confidence: 99%